Ultrasonic assessment of fresh cheese composition - Telis-Romero, J. [UNESP]; Vaquiro, H. A.; Bon, J.; Benedito, J. (Elsevier B.V., 2011)
Fresh cheese composition was assessed by measuring ultrasonic velocity in cheese and cheese blends at different temperatures Twenty types of commercial fresh cheeses with fat contents ranging from 0 2% to 17 6% w b were analyzed Ultrasonic velocity was not only heavily dependent on the composition of the cheese but also on its structure Based on the different effect temperature has on velocity in water and fat a semi-empirical model was used to estimate the cheese composition from velocity measurements at six temperatures ranging from 3 to 29 degrees C The model provided good results for the assessment of the fat (R-2 = 0 984/0 996 RMSE = 46/1 1 for whole and blended cheese respectively) and water (R-2 = 0964/ 0 995 RMSE = 6 5/0 7 for whole and blended cheese respectively) content The ultrasonic measurements could be carried out during the cooling process that takes place after curdling and used as a quality control tool to detect process anomalies in-line (C) 2010 Elsevier Ltd All rights reserved
Keywords: Fresh cheese; Ultrasound; Non-destructive; Composition